Consequences of Workplace Ostracism: A Meta-Analytic Review - Li, Miaomiao; Xu, Xiaofeng; Kwan, Ho Kwong (Frontiers in Psychology, 2021)
Workplace ostracism, which is regarded as “social death,” is rampant in organizations and has attracted significant research attention. We extend the understanding of workplace ostracism by conducting a meta-analysis of studies of the relationships between workplace ostracism and its consequences. We also explore the moderating effects of national culture (i.e., collectivism vs. individualism) and the mediating effects of organization-based self-esteem (OBSE). The results of a meta-analysis of 95 independent samples (N = 26,767) reveal that exposure to workplace ostracism is significantly related to individuals’ attitudes, well-beings, and behaviors. Moreover, the effects of workplace ostracism on belongingness, job satisfaction, emotional exhaustion, organizational citizenship behavior (OCB) toward individuals (OCBI), organizational deviance, and interpersonal deviance are stronger in individualist contexts than in collectivist contexts. However, the relationships between workplace ostracism and organizational identification and OCB are stronger in collectivist contexts than in individualist contexts. Our meta-analytical structural equation modeling also provides evidence of the mediating effects of OBSE on the relationships between workplace ostracism and organizational commitment, job satisfaction, and job performance. The implications and limitations of our study and future research directions are also discussed.